Global oral health course: Perception among dental students in central India - Singh, Abhinav; Purohit, Bharathi (European Journal of Dentistry, 2012)
A questionnaire study was conducted among dental students in Central India. The study population included 264 dental students, who voluntarily completed a questionnaire, comprising of 16 close ended questions. There were 9 questions to judge knowledge and 5 questions for attitude assessment towards global oral health course. Two additional questions were included to assess the willingness to volunteer in international setting; and also, to assess dental student’s perspection on global oral health course. Chi Square test was used to compare between categorical variables. Analysis of Variance (ANOVA) was used to compare mean of knowledge and attitude scores. P value of ≤.05 was considered significant for all statistical analysis. Eighty seven percent of the surveyed students (222) stated that they would consider volunteering their dental skills as a future dentist in international setting. Majority of the students in the present study were not aware about the global oral health status (99.2%) and theoral health care systems of industrialized and emerging economies (99.2%), had not been trained to serve underserved population (68%), had not been trained in global health ethics (70.1%) and none of the students had been trained for cultural competence in addressing international oral health issues (100%). Most of the dental students were not aware, that, WHO created basic package of oral care (63%) about the primary health care strategy (59.5%) and about the role and functions of FDI (66.7%). The majority of students expressed a desire to volunteer their professional services in international settings. However few students knew about WHO’s BPOC or FDI’S role in global oral health. The findings indicate a need for global oral health course among dental students in Central India. (Eur J Dent 2012;6:295-301)
Keywords: Global oral health; primary oral health; pre doctoral dental education; dental volunteer